Upaya Komunikasi Bpjs Kesehatan Kota Padang Dalam Mensosialisasikan Aplikasi Mobile Jkn Melalui Bidang Mutu Layanan Kepesertaan - Fhadiel, Rahmat; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Using the JKN mobile application can provide several conveniences to the public and participants, namely ease of paying and changing membership data, ease of finding information on family participant data, ease of finding information on participant contribution bills, ease of getting information on Health Facilities and ease of submitting complaints, as well as requests for information regarding JKN-KIS. It is hoped that this JKN mobile application can reduce queues at every BPJS Health Branch Office by providing the best service to the community. The BPJS Health Branch Office is a place for the community to complete all administrative activities. Based on the presentation of results based on data and also the results of interviews conducted by researchers, it was concluded that communication efforts in socializing the Mobile JKN application BPJS Health carried out direct socialization to the public about the uses and advantages of using the Mobile JKN application because in the current era of digitalization all activities or matters have been implemented. Through the media and BPJS Health created the Mobile JKN application to help the public so that it is no longer difficult to use the JKN-KIS card, although some people are still unfamiliar with this, BPJS Health carried out outreach to community groups by providing educational material on using the Mobile JKN application.